Using of Whey Proteins as Antioxidant in Some Food Products - Nahla Tariq Khalid (Journal of Global Pharma Technology, 2019)
Oxidation of foodstuffs has become an issue concerning with food quality and consumer health, specifically in dairy products which contain a percentage of fat. The present study aimed to use whey proteins concentration (WPC) as additive to some samples of dairy products selected from local market. Adding WPC to these products with different concentration demonstrated a good activity of whey proteins concentration as antioxidant. Lipid oxidation measured on the basis of malondialdehyde by determining thiobarbaturic acid (TBA). Results obtained show differences in TBA value before and after adding WPC. Adding WPC reduced the TBA value about half in collected samples, and that led us that the period of lipid oxidation with adding WPC will be longer than these samples used without adding WPC. Using this method to protect food products from lipid oxidation by adding WPC has been proved the activity of whey proteins as antioxidant in this research.Keywords: Whey proteins, Antioxidant activity, Foods products.